Lead removal from aqueous solution by natural and pretreated clinoptilolite:: Adsorption equilibrium and kinetics - Gunay, Ahmet; Arslankaya, Ertan; Tosun, Ismail (ELSEVIER, 2007)
Adsorption of Pb(II) ions from aqueous solution onto clinoptilolite has been investigated to evaluate the effects of contact time, initial concentration and pretreatment of clinoptilolite on the removal of Pb(II). Experimental data obtained from batch equilibrium tests have been analyzed by four two-parameter (Freundlich, Langmuir, Temkin and Dubinin-Radushkevich), four three-parameter (Redlich-Peterson, Sips, Toth and Khan) isotherm models, and kinetic models including the pseudo-first order, the pseudo-second order and Elovich equations using nonlinear regression technique. Of the two-parameter isotherms, Temkin isotherm was the best to describe the experimental data. Three-parameter isotherms have higher regression coefficients (>0.99) and lower relative errors (<5%) than two-parameter isotherms. The best fitting isotherm was the Sips followed by Toth and Redlich-Peterson isotherm equations. Maximum experimental adsorption capacity was found to be 80.933 and 122.400 mg/g for raw and pretreated clinoptilolite, respectively, for the initial concentration of 400 mg/L. Kinetic parameters; rate constants, equilibrium adsorption capacities and related coefficients for each kinetic model were evaluated according to relative errors and correlation coefficients. Results of the kinetic studies show that best fitted kinetic models are obtained to be in the order: the pseudo-first order, the pseudo-second order and Elovich equations. Using the thermodynamic equilibrium coefficients, Gibbs free energy of the Pb(II)-clinoptilolite system was evaluated. The negative value of change in Gibbs free energy (Delta G degrees) indicates that adsorption of Pb(II) on clinoptilolite is spontaneous. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: adsorption; isotherm; kinetic; clinoptilolite; lead; ION-EXCHANGE; HEAVY-METALS; WASTE-WATER; AMMONIUM REMOVAL; ZEOLITE; BIOSORPTION; COPPER(II); CADMIUM; GASES; MOSS; Engineering; Environmental Sciences & Ecology